E-COMMERCE BERBASIS WEB DENGAN API FACEBOOK PADA TOKO BANGUNAN BERKAH - Anwar, Sariyun Naja; Purnomo, Sigit (Information Technology and Telematics, 2019)
Abstract - The sales process at Toko Bangunan Berkah is still using a conventional system, that is, customers who want to buy and find out the product directly come to Toko Bangunan Berkah. In addition, sales are still using manual methods. One solution to deal with these obstacles is to use web-based online sales so that it will make it easy for customers to order goods without having to come directly to Toko Bangunan Berkah. With the use of Facebook API or Graph API, it’s expected to make it easier for customers who want to register an account or login to the Toko Bangunan Berkah website. The system development method used in this study is Waterfall and system design using UML. Programming used in the development of this system uses HTML, PHP, and MySQL programming languages while to create an attractive and responsive display using the bootstrap framework.